Dynamic modelling and analysis of post-combustion CO2 chemical absorption process for coal-fired power plants - Lawal, Adekola; Wang, Meihong; Stephenson, Peter; Koumpouras, G.; Yeung, Hoi (Elsevier Science B.V., Amsterdam., 2011)
Post-combustion capture by chemical absorption using MEA solvent remains the only commercial technology for large scale CO2 capture for coal-fired power plants. This paper presents a study of the dynamic responses of a post- combustion CO2 capture plant by modelling and simulation. Such a plant consists mainly of the absorber (where CO2 is chemically absorbed) and the regenerator (where the chemical solvent is regenerated). Model development and validation are described followed by dynamic analysis of the absorber and regenerator columns linked together with recycle. The gPROMS (Process Systems Enterprise Ltd.) advanced process modelling environment has been used to implement the proposed work. The study gives insights into the operation of the absorber- regenerator combination with possible disturbances arising from integrated operation with a power generation plant. It is shown that the performance of the absorber is more sensitive to the molar L/G ratio than the actual flow rates of the liquid solvent and flue gas. In addition, the importance of appropriate water balance in the absorber column is shown. A step change of the reboiler duty indicates a slow response. A case involving the combination of two fundamental CO2 capture technologies (the partial oxyfuel mode in the furnace and the post-combustion solvent scrubbing) is studied. The flue gas composition was altered to mimic that observed with the combination. There was an initial sharp decrease in CO2 absorption level which may not be observed in steady-state simulations. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: CO2 capture Post-combustion Chemical absorption Dynamic modelling Coal-fired power plant aqueous monoethanolamine capture performance simulation gas